2018
DOI: 10.1177/0886260518780782
|View full text |Cite
|
Sign up to set email alerts
|

Violent and Nonviolent Crimes Against Sex Workers: The Influence of the Sex Market on Reporting Practices in the United Kingdom

Abstract: Previous research has shown that sex workers experience extremely high rates of victimization but are often reluctant to report their experiences to the police. This article explores how the markets in which sex workers operate in the United Kingdom impact upon the violent and nonviolent crimes they report to a national support organization and their willingness to report victimization to the police. We use a secondary quantitative data analysis of 2,056 crime reports submitted to the U.K. National Ugly Mugs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
2
16
0
1
Order By: Relevance
“…Where clients contact providers matter a great deal. Street sex markets draw more vulnerable sellers and buyers with fewer financial and social resources, and both parties, but especially the workers, are likely to encounter violence in the environment by police or criminals (Connelly, Kamerāde, & Sanders;Deering et al, 2014;Weitzer, 2009). On the other hand, print ads, and more recently, digital communications provide distance in time and space allowing both buyer and seller to gather more information, be more selective and screen out dangerous or undesireable clients and situations (Armstrong, 2014;Scott Cunningham & Kendall, 2011;Monto & Milrod, 2014;Nelson, Hausbeck Korgan, Izzo, & Bessen, 2019;Sanders, 2008aSanders, , 2008b.…”
Section: Diversity In Prostitution Marketsmentioning
confidence: 99%
“…Where clients contact providers matter a great deal. Street sex markets draw more vulnerable sellers and buyers with fewer financial and social resources, and both parties, but especially the workers, are likely to encounter violence in the environment by police or criminals (Connelly, Kamerāde, & Sanders;Deering et al, 2014;Weitzer, 2009). On the other hand, print ads, and more recently, digital communications provide distance in time and space allowing both buyer and seller to gather more information, be more selective and screen out dangerous or undesireable clients and situations (Armstrong, 2014;Scott Cunningham & Kendall, 2011;Monto & Milrod, 2014;Nelson, Hausbeck Korgan, Izzo, & Bessen, 2019;Sanders, 2008aSanders, , 2008b.…”
Section: Diversity In Prostitution Marketsmentioning
confidence: 99%
“…This body of research not only exposes sex workers' heightened risk of physical violence -from (a minority of) clients, vigilantes, police officers, controllers, and others (Campbell and Stoops, 2010;Kinnell, 2008) -but also, how sex workers are deterred from reporting victimisation. This may be due to the (perceived) risk of: arrest, the arrest of their co-workers and/or clients, the closure of the premises in which they work, and/or public identification (Boff, 2012;Connelly, Kamerade and Sanders, 2018;Klambauer, 2018). The sex work studies field is thus burgeoning with work that contests the marginalisation and stigmatisation of sex workers.…”
Section: Key Contributions Of Sex Work Scholarshipmentioning
confidence: 99%
“…This is particularly low when compared to the documented level of reporting to the police for reports from sex workers reporting into the NUM scheme in the UK. Connelly et al (2018) having analysed 2056 reports submitted to NUM between 2011 and 2016 and found that in nine out of ten cases (90%), the sex worker had given anonymous consent to share report data with the police, whereas in only two out of ten cases (20%) gave their full consent (permission to report formally) compared to no more than 1.81% in any of the years examined for UM. Whilst reporting to the police has been consistently low, UM data indicate that reporting levels have not improved since Ireland introduced the 2017 Act.…”
Section: Sharing Information With and Reporting To The Policementioning
confidence: 99%